Activity of methanogenic archaea under simulated Mars analog conditions - Schirmack, Janosch (Universität Potsdam, 2015)
Assumed comparable environmental conditions of early Mars and early Earth in 3.7 Ga ago – at a time when first fossil records of life on Earth could be found – suggest the possibility of life emerging on both planets in parallel. As conditions changed, the hypothetical life on Mars either became extinct or was able to adapt and might still exist in biological niches. The controversial discussed detection of methane on Mars led to the assumption, that it must have a recent origin – either abiotic through active volcanism or chemical processes, or through biogenic production. Spatial and seasonal variations in the detected methane concentrations and correlations between the presence of water vapor and geological features such as subsurface hydrogen, which are occurring together with locally increased detected concentrations of methane, gave fuel to the hypothesis of a possible biological source of the methane on Mars. Therefore the phylogenetically old methanogenic archaea, which have evolved under early Earth conditions, are often used as model-organisms in astrobiological studies to investigate the potential of life to exist in possible extraterrestrial habitats on our neighboring planet. In this thesis methanogenic archaea originating from two extreme environments on Earth were investigated to test their ability to be active under simulated Mars analog conditions. These extreme environments – the Siberian permafrost-affected soil and the chemoautotrophically based terrestrial ecosystem of Movile cave, Romania – are regarded as analogs for possible Martian (subsurface) habitats. Two novel species of methanogenic archaea isolated from these environments were described within the frame of this thesis. It could be shown that concentrations up to 1 wt% of Mars regolith analogs added to the growth media had a positive influence on the methane production rates of the tested methanogenic archaea, whereas higher concentrations resulted in decreasing rates. Nevertheless it was possible for the organisms to metabolize ...